Poly(N-vinylcaprolactam) Nanogels with Antiviral Behavior against HIV-1 Infection - Macchione, Micaela Alejandra (2019)
Stimuli-responsive nanogels offer promising perspectives for the development of next generation formulations for biomedical applications. In this work, poly(N-vinylcaprolactam) nanogels were synthesized varying the concentration of monomer and crosslinking agent. Thus, the inhibitory effect of poly(N-vinylcaprolactam) nanogels against HIV-1 infection is presented for the first time. In particular, we have demonstrated that one of the synthesized poly(N-vinylcaprolactam) nanogels with initial concentration of 80 mg of vinylcaprolactam and 4% of crosslinking agent shows antiviral behavior against HIV-1 infection since this nanogel inhibits the viral replication in TZM.bl target cells.